HEALTH AS AN ELEMENT OF HUMAN CAPITAL AND A FACTOR OF ECONOMIC GROWTH - Cherevko Г.; Vovk І. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The purpose of this article is to present research results of the main approaches to interpreting the essence of human potential and health as its main element and factor of the functioning efficiency. The main task of the conducted research was to analyze, systematize and summarize available information on the essence and structure of human potential in the context of importance and role of health in it, and to present the obtained results in the form of conclusions that can be useful for different levels of power authorities and administrative economic bodies, especially for enterprises seeking to improve quality of their human potential as a basis for further economic growth. The methodology of the research conducted on the topic of this article is based on application of the principles of dialectical method of scientific research in the best possible combination with analysis and synthesis, induction and deduction, scientific abstraction, organic integrity of history and logic in economic researching by using monographic and descriptive methods, as well as methods of generalization, comparison, scientific predictions and forecasting. The main sources of information used in the course of the conducted research included materials of official information sources, publications of domestic and foreign scientists related to the identified research direction, and the results of authors’ personal observations. The research has clarified evolution of the concept and structure of the category of human capital and the place of health in it, as well as its impact on the level of population’s well-being, which is formed as a result of the combined effect of economic growth and health status. The scientific novelty of the results of the conducted research consists in the formed dependence, having the character of a circular closed cycle, between the level of health, the quality of human capital and economic growth. The most promising direction of the further research on the impact of health on economic growth due to the quality of human capital, and impact of economic growth on health may revealed in development of the methodology for determining the tightness of the mentioned relation at each link of the established chain of dependencies.